Analysis of Direct Marketing and Personal Selling Strategy at PT. Duta Merpati Indonesia - Nisa, Maghfirotun; Reviandani, Wasti (Dinasti International Journal of Digital Business Management, 2024)
This study analyzes the Direct Marketing and Personal Selling strategies at PT. Duta Merpati Indonesia and their impact on sales and customer relationships. Using a qualitative approach, data were collected through in-depth interviews, direct observation, and document analysis. The results showed that Direct Marketing through email and social media is effective in reaching customers and increasing responses, despite challenges such as the perception of messages as spam. Personal Selling has been shown to build strong customer relationships, but is constrained by the lack of an accurate customer database, making it difficult to measure the success of the strategy. Both strategies contribute significantly to increasing sales and customer loyalty. The challenges identified, such as the need for improved digital infrastructure and sales force training, require special attention. Optimal implementation of both strategies can create more value for customers and drive the company's sales growth.